2020
DOI: 10.1039/c9nr08726e
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical heterostructure of SnO2 confined on CuS nanosheets for efficient electrocatalytic CO2 reduction

Abstract: Hierarchical heterostructure of SnO2 confined on ultrathin CuS nanosheets for efficient electrocatalytic CO2 reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 80 publications
0
28
0
Order By: Relevance
“…To further evaluate the role of chemical states in R‐Cu 2 SnS 3 , X‐ray photoelectron spectroscopy (XPS) was performed. The negatively shift XPS peaks of Cu 2p and the constant XPS peaks of Sn 3d suggested that the formation of the heterojunction nanosheets can efficiently enhanced the negative potential tolerance of Sn 4+ through the electron self‐flow between Cu + and Sn 4+ during the CO 2 RR process (Figure 4 f and g) [8] . These results also demonstrated that the Sn 4+ held the same valence state during the CO 2 RR process for it benefited from the protection of Cu + with more positive redox potential than Sn 4+ and the strong electron interaction between the CuS, Cu 2 O and SnO 2 (Figure S14) [18] .…”
Section: Resultsmentioning
confidence: 99%
“…To further evaluate the role of chemical states in R‐Cu 2 SnS 3 , X‐ray photoelectron spectroscopy (XPS) was performed. The negatively shift XPS peaks of Cu 2p and the constant XPS peaks of Sn 3d suggested that the formation of the heterojunction nanosheets can efficiently enhanced the negative potential tolerance of Sn 4+ through the electron self‐flow between Cu + and Sn 4+ during the CO 2 RR process (Figure 4 f and g) [8] . These results also demonstrated that the Sn 4+ held the same valence state during the CO 2 RR process for it benefited from the protection of Cu + with more positive redox potential than Sn 4+ and the strong electron interaction between the CuS, Cu 2 O and SnO 2 (Figure S14) [18] .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the improvement in catalytic activity by increasing dispersion of active sites owing to confinement effect has also been extended to electrocatalytic reduction of CO 2 . [45,46] Especially, Tuo e al reported a new strategy to synthesize metal porphyrin-hybridized porous and ultra-thin carbon nanosheets (MPPCN) by the confinement function of the layered template. In the preparation process, the layered confinement reaction protects the coordination structure of metal and nitrogen atoms during subsequent hightemperature treatment while ensuring the formation of ultrathin structures.…”
Section: Increasing Metal Dispersionmentioning
confidence: 99%
“…Such Sn sites with high charge density can attract CO 2 molecules, lower the activation energy of CO 2 RR, and boost the conversion of intermediates. Moreover, the interfacial electron transfer is promoted by the strong electronic interactions between Sn species and the CN substrate [24] . On the other hand, the SnO x layer can suppress HER to a certain extent, but a metal oxide layer with excessive thickness would also decrease the conduction and enhance the evolution of H 2 [14] .…”
Section: Resultsmentioning
confidence: 99%